1998
DOI: 10.1037/0022-006x.66.6.1023
|View full text |Cite
|
Sign up to set email alerts
|

Mild closed-head injury in children and adolescents: Behavior problems and academic outcomes.

Abstract: The issue of whether mild head injuries (HIs) in children cause behavior problems and poor scholastic performance is controversial. This study included 119 children (range = 8-16 years old) with HI, 114 with other injuries, and 106 with no injury (NI). Behavioral functioning was assessed with the Child Behavior Checklist; academic functioning, with school grades and standardized testing. Higher T scores were found for both injury groups versus NI participants on preinjury behavioral status. All 3 groups' behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 27 publications
3
44
0
3
Order By: Relevance
“…Furthermore, some studies use children with mild TBI as 'controls' for children with severe TBI [12]. There have been a number of studies of mild TBI which provide conflicting results, and likely outcomes following mild TBI remain unclear [13]. However, the term 'mild' TBI can be ambiguous, some studies include patients attending Accident and Emergency departments who return directly to home after treatment, whereas others recruit patients who have been admitted to hospital for neurological observation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies use children with mild TBI as 'controls' for children with severe TBI [12]. There have been a number of studies of mild TBI which provide conflicting results, and likely outcomes following mild TBI remain unclear [13]. However, the term 'mild' TBI can be ambiguous, some studies include patients attending Accident and Emergency departments who return directly to home after treatment, whereas others recruit patients who have been admitted to hospital for neurological observation.…”
Section: Introductionmentioning
confidence: 99%
“…De fait, pour eux, il est clair que la persistance, ou du moins la présence, de certaines conséquences engendrées par le TCC sont attribuables à des facteurs préexistants chez les enfants et adolescents tels qu'avoir déjà vécu un TCC dans le passé, avoir des antécédents de problème neurologique, d'apprentissage ou psychosocial (Anderson et al, 2005;Light et al, 1998;Ponsford et al, 1999).…”
Section: Constats Et Discussionunclassified
“…« Un jeune qui n'était pas actif socialement, qui n'avait pas de loisirs, qui n'avait pas d'amis, bien là, il n'en aura pas plus », affirme une professionnelle. Ainsi, il appert qu'à nouveau, la préexistence de problèmes chez l'enfant ou l'adolescent a un impact sur la présence et la persistance de certaines conséquences reliées au TCC (Anderson et al, 2005;Light et al, 1998;Ponsford et al, 1999).…”
Section: Constats Et Discussionunclassified
See 1 more Smart Citation
“…Research on the academic effects of concussion has generally shown no adverse long-term outcomes (6,7). In most cases, concussion symptoms and cognitive difficulties will improve in a matter of days (8).…”
Section: Principles For Return To Learn After Concussionmentioning
confidence: 99%